Egy oktatástörténeti kuriózum: Jenei G. István iskolai jegyzetei - Erdős, Zoltán; Mátyás-Rausch, Petra (Per Aspera ad Astra, 2018)
The study presents the lecture notes from the Kolozsvár (Cluj-Napoca) University Library, which belonged to István G. Jenei, a Calvinist priest of Zilah (Zalău), Kolozs (Cluj), and then of Zabol, the dean of the Diocese of Kolozs-Katola (Cluj-Kalotan). Jenei studied at the Reformed College in Várad (Oradea), and then enrolled in University of Franeker. The manuscripts were produced in Oradea in 1626–1627 and can be divided into three divisions: the first part of the material consist of 24 theological disputes, the second part is an extract from the work of Robert Parker De politeia ecclesiastica Christi et hierarchica opposite libri tres, and the third contains 13 disputes from the field of logic. The notes give light to the methods of theological education, the important role of the disputes and the nature of the collective labour of the students. The owner of the notes has not replaced the material for a long time, and has also added new notes decades later, which shows its value. Thus, a booklet of Hungarian records from between 1657–1661 and an outline of the Latin eulogy given at the burial of Imre Pápai Páriz were implemented to the blank pages. The topics of the theological and logic debates are listed in the appendix of the study; furthermore the historical records and the eulogy can be red in the transcript of the text.